2009
DOI: 10.1080/14992020902894541
|View full text |Cite
|
Sign up to set email alerts
|

Hearing, use of hearing protection, and attitudes towards noise among young American adults

Abstract: The purpose of the present study was to investigate possible associations between college students' attitudes, risk-taking behaviour related to noisy activities, and hearing problems such as threshold shifts or self-experienced hearing symptoms. The sample included 258 students aged between 17 and 21 enrolled at the University of Pennsylvania, USA. A questionnaire measuring attitudes towards noise, use of hearing protection, and self-reported hearing symptoms was distributed among the students. After completin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 14 publications
8
63
3
1
Order By: Relevance
“…[12] A study of 258 American adolescents indicated that 26% had thresholds poorer than the screening level of 20 dBHL. [13] Attitudes were also significantly related to self-experienced hearing symptoms, but not to threshold shifts itself, indicating that self-experienced symptoms may function as a cue to attitudinal and behavioral change, whereas smaller and probably unnoticed threshold shifts do not appear to have any impact on attitudes and behaviors. Additionally, the study revealed that hearing protection was preferred to a greater degree when using firearms, mowing lawns, and working with noisy tools, than when attending concerts and clubs.…”
Section: Introductionmentioning
confidence: 94%
“…[12] A study of 258 American adolescents indicated that 26% had thresholds poorer than the screening level of 20 dBHL. [13] Attitudes were also significantly related to self-experienced hearing symptoms, but not to threshold shifts itself, indicating that self-experienced symptoms may function as a cue to attitudinal and behavioral change, whereas smaller and probably unnoticed threshold shifts do not appear to have any impact on attitudes and behaviors. Additionally, the study revealed that hearing protection was preferred to a greater degree when using firearms, mowing lawns, and working with noisy tools, than when attending concerts and clubs.…”
Section: Introductionmentioning
confidence: 94%
“…Adolescents fi rst must become aware that listening to high-volume music may cause hearing damage and that they personally are at risk for hearing loss before the promotion of protective behaviours is useful (Vogel et al, 2009). In addition, selfexperienced symptoms after recreational noise exposure might lead to greater awareness (Widen et al, 2009), which can change personal listening behaviour in order to protect hearing. Moreover, if hearing deterioration can be shown at an early stage, actions can be taken to prevent further hearing loss (Meyer-Bish, 1996).…”
mentioning
confidence: 99%
“…Adolescents' with permanent tinnitus or sound sensitivity had less tolerant attitudes toward loud music. In an earlier study, Widén et al, [20] found that individuals with self-perceived auditory symptoms such as sound sensitivity and hearing loss generally had less tolerant attitudes toward loud music associated with youth culture, e.g. discotheques, concerts and gyms.…”
Section: Discussionmentioning
confidence: 98%
“…Widén et al, [20] concludes that having experienced self-perceived auditory symptoms may be more important than just information to change young people's attitudes and behaviors. It is suggested that in addition to information, e.g.…”
Section: Discussionmentioning
confidence: 98%